Tonsillar Schwannoma: a rare case report - Shukla, Stuti; Pathak, Vivek K.; Sharma, Himani; Arora, Kanika; Rizvi , Sama (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
A Schwannoma is a benign, locally aggressive tumor that occurs due to the proliferation of Schwann cells of the nerve sheath. These tumors may involve any cranial nerve and hence are routinely missed on diagnosis. We report a rare case of a young adult female with unilateral tonsillar fossa mass which was excised by transoral approach, and histopathology reported to be a tonsillar schwannoma. Hence, it is necessary to be aware of these rare benign tumors as they can mimic a tonsillar hypertrophy.